Development of sustained-release extemporaneous moxifloxacin loaded commercial soft hydrogel contact lenses - Duy Toan Pham; Pratthana Chomchalao; Kunasin Bunneramit; Phurichaya Kladcharoen; Rossukon Khotcharrat; Waree Tiyaboonchai (Heliyon)
Eye infections such as Acanthamoeba keratitis and bacterial keratitis are serious diseases that could lead to severe, sight-threatening complications. Although moxifloxacin eye drops (0.5 % w/v) is accepted for clinical treatments of these infections, the frequent administration is challenging to achieve the adequate dose due to the limitations of low ocular bioavailability and short retention time. To circumvent these issues, this study developed the extemporaneous moxifloxacin loaded commercial soft hydrogel contact lenses with sustained-release property. The simple soaking method was employed on five common available contact lenses of Acuvue, Biomedics, Maxim, Soflens, and Biotrue, which were immersed in the standard moxifloxacin eye drops solutions. Amongst them, three contact lenses (Acuvue, Biomedics, and Maxim) showed high drug loading of ∼2 mg and adequate controllable drug release for 24 h with Maxim possessing the highest release rate, and maintained the effective drug therapeutic level for at least 12 h. Kinetically, both the moxifloxacin loading and releasing processes followed the Higuchi model, with the diffusion mechanism governing the drug behaviors. Isothermally, the moxifloxacin molecules were adsorbed onto the contact lenses surfaces via physical adsorptions by weak interactions of van der Waals forces, ionic bonding, and hydrophobic interactions. Furthermore, both the eye drops brands (Moximac and Zomoxin), the loading pH (6.7 and 6.0), and the loading time (24 h and 2 h) had no significant effects on the loading and release of moxifloxacin, indicating the system versatility. Conclusively, the extemporaneous moxifloxacin loaded contact lenses, with a duration of action of at least 12 h, could be further explored to become a potential treatment for eye infections.